2019
DOI: 10.1016/j.dib.2019.103862
|View full text |Cite
|
Sign up to set email alerts
|

Data describing effects of perinatal exposure to bisphenol S on a peripubertal estrogen challenge in intact female CD-1 mice

Abstract: Bisphenol S (BPS) is an analogue of bisphenol A (BPA), used in consumer products including food packaging and thermal paper. Like BPA, BPS is an estrogen receptor agonist and exposures during perinatal development have been shown to alter growth and morphology of the mouse female mammary gland prior to puberty and in adulthood. Reported here are data describing the effect of exposure to low doses of BPS (2, 200 or 2000 μg/kg/day) during perinatal development on morphology and gene expression in the mammary gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…These data showed that the lowest dose of BPS676(2 µg/kg bw/day) disrupted male mammary gland development with different susceptibility 677 between the right and left glands, leading the authors to propose male mice exposed to low-678dose BPS as a model to study unilateral gynecomastia observed in boys during puberty. Lastly, 679Kolla & Vandenberg (2019) showed that perinatal treatment from GD 9 to PND 2, or a 680 challenge with EE2 at a peripubertal period from PND 21 to PND 30, did not affect the number 681 or total area of TEBs, whereas the ductal area was decreased. Similar exposures in males682 showed different susceptibility to BPS and EE2 in the right and left glands (Kolla et al, 2019).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…These data showed that the lowest dose of BPS676(2 µg/kg bw/day) disrupted male mammary gland development with different susceptibility 677 between the right and left glands, leading the authors to propose male mice exposed to low-678dose BPS as a model to study unilateral gynecomastia observed in boys during puberty. Lastly, 679Kolla & Vandenberg (2019) showed that perinatal treatment from GD 9 to PND 2, or a 680 challenge with EE2 at a peripubertal period from PND 21 to PND 30, did not affect the number 681 or total area of TEBs, whereas the ductal area was decreased. Similar exposures in males682 showed different susceptibility to BPS and EE2 in the right and left glands (Kolla et al, 2019).…”
mentioning
confidence: 95%
“…Intra-ductal hyperplasia in adult mammary glands was also observed at both doses of 667 BPS and EE2. Similar effects in adults were previously observed for BPA exposure(Soto et 668 al., 2013).669Similar investigations were carried out in F1 males exposed to BPS (2 and 200 µg/kg bw/day) 670 over the same exposure period (GD 9 -PND 20)(Kolla et al, 2019). At embryonic day (ED) 671 16, the number of androgen receptor (AR)-positive cells in the mesenchyme was reduced in a 672 dose-dependent manner.…”
mentioning
confidence: 99%